The language of leadership : Exploring Malaysian student leaders' word choices and styles - Sharipah Syakila, Syed Shaharuddin (2024)
Effective leadership hinges on strategic communication, incorporating both verbal and non-verbal cues that empower leaders to inspire collaboration, manage conflict, and influence others. In Malaysian boarding schools, student leaders navigate multicultural settings where cultural norms, societal expectations, and academic pressures shape their communication styles. Despite the complexity of these environments, research on how these factors influence student leadership communication remains limited. This study explores how Malaysian student leaders utilize language, particularly word choice, inclusive expressions, and linguistic framing, to foster collaboration, influence peers, and manage conflicts within their distinctive institutional contexts. Guided by Goffman’s framing theory, this study collected data through focus group discussions and interviews with student leaders from selected Malaysian boarding schools. Findings reveal that student leaders adapt their language styles to promote inclusivity, maintain harmony, and assert authority. They employ culturally appropriate language, frame their messages to support conflict resolution, and use non-verbal cues such as tone modulation and body language to enhance peer engagement and strengthen their leadership presence. This study contributes to leadership training programs by highlighting the importance of inclusive communication, cultural sensitivity, and effective framing techniques. It offers practical recommendations for youth leadership development and cross-cultural communication strategies within the context of Malaysian boarding schools